INSTRUMENTASI VIRTUAL MENGGUNAKAN LABVIEW DAN SOUNDCARD - stevani agnesia sigiro (Saintia Fisika, 2013)
The high cost of instrumentation equipment such as signal generate and oscilloscope makes it difficult to have it, especially for human purposes in laboratory practicum. Besides the price is quite expensive, instrumentation equipment is expected to be removable (portable). To overcome the problem of price and portability, so in this study used soundcard as a virtual signal generate and virtual oscilloscope using LabVIEW Evaluation software version 11 (Laboratory Virtual Instrumentation Engineering Workbench). The results showed that the virtual signal generate is designed to have good performance with average errors of 0.2% and 0.0015% accuracy in the frequency range 20 Hz - 20 kHz. While in the same frequency range, testing on a virtual oscilloscope measurements produced a mean error of 0.0024%. In addition to reading measurement accuracy and waveform generation, virtual signal generate and virtual oscilloscope can display multiple waveforms such as sine wave, square wave, sawtooth wave, and triangle wave. Keywords : Soundcard, LabVIEW, Virtual Signal generator, Virtual Oscilloscope